A randomized clinical trial testing the effectiveness of an adapted online HIV/AIDS prevention intervention among Latino men - Patria Rojas; Weize Wang; Jose F. Colon-Burgos; Yajaira A. Cabrera Tineo; Gira Ravelo; Osmari Beatriz Novoa; María C. Pinzón-Iregui; Berenice Castillo; Maria A. Khalona; Juan S. Castillo; Michelle Robinson; Victoria Behar-Zusman (Scientific Reports)
Abstract Several factors exacerbate the risk of HIV infection among Latino men, including low HIV/AIDS knowledge, low perception of HIV risk, and higher related stigma, as well as limited access to health care prevention services. HoMBRES de Familia was a randomized controlled trial to adapt and test the efficacy of an intervention that was implemented with Latino men in semi-rural and urban areas of Miami-Dade County. The HoMBRES de Familia intervention, conducted during the COVID-19 pandemic, aimed to reduce the risk of substance abuse, intimate partner violence, and HIV/AIDS (i.e., SAVA syndemic) among Latino men. Participants (n = 122) were randomly assigned to either the intervention or the control group with a 1:1 ratio. Participants were interviewed by phone in the language of their preference at baseline and at 6-month follow-up after the intervention. Control group received one diabetes prevention session while the HoMBRES de Familia intervention consisted of four video sessions on HIV, substance use, and intimate partner violence prevention. Results suggest that this intervention was effective in increasing HIV knowledge and HIV self-efficacy, as well as reducing risky sexual behaviors among the intervention group participants. We discuss possible effects of the pandemic on participants’ levels of stress and alcohol use quantity and potential impacts on problematic drinking for Latino men.